DIFFERENTIAL MORTALITY AND INEQUALITIES IN HEALTH SERVICES ACCESS IN MAINLAND PORTUGAL - VIDAL, Diogo Guedes; Pontes, Manuela; Barreira, Esmeralda; Oliveira, Gisela M; Maia, Rui Leandro (Finisterra, 2019)
The guarantee of the right to health protection, with the priority of suppressing health inequalities, is a main goal of the Portuguese National Health Service. In this context, the health care access equity in mainland Portugal continues to be a challenge for public health policies, with a littoral territory where health services are concentrated and interior depopulated zones, stripped of health services and condemned to a physical and social isolation. Based on year 2011 data from PORDATA , the present work studies how mortality is related to health services distribution - namely hospital infrastructures, health centres and health professionals - and with population characteristics related to illiteracy and ageing. The results show a strong association between mortality and health services distribution, highlighting that mortality increases with the decrease of health services distribution, worsening when related to population illiteracy and ageing. Results reveal the importance to draw up local level public policies, focused on the socio-cultural specificities of the territories, which are mainly materialized in a distribution of health services closer to isolated populations according to their needs.